2007
DOI: 10.1088/0264-9381/24/9/001
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to detect gravitational waves with atom interferometers?

Abstract: We investigate the possibility of using atom interferometers to detect gravitational waves. We discuss the interaction of gravitational waves with an atom interferometer and analyse possible schemes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 41 publications
5
88
0
Order By: Relevance
“…This v L T term is essentially the same term that has been found by previous authors (e.g. [27]). We will not use this term for the signal in our proposed experiment as it is smaller than the first term.…”
Section: B Resultssupporting
confidence: 83%
“…This v L T term is essentially the same term that has been found by previous authors (e.g. [27]). We will not use this term for the signal in our proposed experiment as it is smaller than the first term.…”
Section: B Resultssupporting
confidence: 83%
“…This is essentially the same term that has been found by previous authors (e.g. [27]). It can loosely be thought of as arising from the effect of the gravitational wave on the atom's trajectory, the effective 'force' on the atom.…”
Section: B Resultssupporting
confidence: 84%
“…The work of [26] and [27] described atom interferometers which used light pulse interferometry. However, these authors did not consider the effect of the gravitational wave on the light pulses used to execute the interferometry.…”
Section: Conclusion a Comparison With Previous Workmentioning
confidence: 99%
“…The role of atom interferometers in gravitational wave detection has been previously studied [16,17,18,19,20,21] and these authors concluded that atom interferometers would need an unrealistic atom flux to probe interesting regions of the gravitational wave spectrum. Our proposal differs significantly from these efforts owing to the central role played by light pulse atom interferometry in this setup.…”
Section: Methodsmentioning
confidence: 99%